Psychotherapy in Shreemad-Bhagwad-Geeta (Krishna-Upachaar for Arjun-Rog) - Risal, Ajay (Bodhi: An Interdisciplinary Journal, 2024)
Shreemad-Bhagwad-Geeta (The Geeta) is the most influential scripture not only in the cultural, religious and theoretical aspects, but also in the academic, philosophical, and practical phases of individual and social lifes. Currently, there are discussions among academicians, philosophers, and mental health practitioners to utilize this discourse also for psychological treatment. Krishna-Arjun communication in the Geeta is almost similar to the client-therapist relationship in the modern day clinical practice. The Geeta's dialogue transpired in the battlefield (Kurukshetra) of the famous Mahabharat war, when one of the most influential warriors of the Pandav side, Arjun, became psychologically disturbed (melancholic), and decided to flee. His charioteer, Krishna, then assumed the therapist's position and provided the essential counseling (therapy) to bring Arjun back to the war. The Krishna-Arjun conversation during that time can be easily interpreted in the modern psychotherapeutic procedures: supportive, cognitive, behavioral, grief-resolution, motivational enhancement, hypnosis, etc. Krishna used an eclectic approach to heal Arjun’s mind and motivate him towards his Kshetriya duty. Thus, I see the Geeta as a form of Krishna’s treatment to heal Arjun’s mind, i.e., Krishna-Upachaar for the Arjun-Rog. This paper tries to establish this proposition.